LINKING FINANCIAL LITERACY TO ENTREPRENEURIAL SUCCESS: A SYSTEMATIC REVIEW OF THEORETICAL AND EMPIRICAL EVIDENCE (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Financial literacy is increasingly recognized as a crucial factor influencing the success of micro, small and medium enterprises (MSMEs), especially in developing countries. Despite the importance of financial literacy, many entrepreneurs still lack adequate knowledge, which hinders their decision-making abilities and business performance.This study aims to investigate the relationship between financial literacy and financial performance of MSMEs, with a focus on identifying mediating and moderating factors that influence this relationship. A systematic literature review (SLR) was conducted by analyzing peer-reviewed articles published between 2016 and 2024. Data were collected from leading databases, including Scopus and Web of Science. Thematic analysis was applied to synthesize findings and identify key patterns in the literature.This review reveals a positive correlation between financial literacy and business performance indicators such as profitability and revenue growth. In addition, factors such as managerial competence and access to financial resources are found to act as mediators and moderators in this relationship, enhancing the effectiveness of financial literacy in improving business outcomes.These findings emphasize the need for targeted financial literacy programs for MSMEs, which can significantly improve their financial management practices and overall performance. This study contributes to the theoretical framework of financial literacy and offers practical implications for policymakers and business educators in promoting sustainable entrepreneurship.